The theory of risk as a new basis for international responsibility in the face of environmental damage - Didi, Brahim (Art Law and Accounting Reporter, 2025)
This paper argues that the “theory of risk” (objective/strict responsibility) offers a practical modern basis for international responsibility for environmental damage caused by hazardous activities that are lawful under international law. Because proving fault and illegality is often difficult in transboundary pollution and technologically complex harm, the paper explains how liability can be grounded primarily in the occurrence of damage and a causal link, aiming to secure compensation and restore balance between the acting state’s interests and the injured state’s rights. It also reviews the main doctrinal debate over transferring risk-based liability into international law and surveys its expression in international practice through treaty regimes (notably space liability, oil pollution, and hazardous waste) and selected judicial/arbitral examples involving transboundary harm.